Experimental Study on Thermal Properties of Nano-TiO2 Embedded Paraffin (NEP) for Thermal Energy Storage Applications. (2020) - Manoj Kumar, P.; Mylsamy, K.; Saravanakumar, P.T.; Anandkumar, R.; Pranav, A.
Abstract: Paraffin is widely finding its application as thermal energy storage material, since they possess superior thermophysical properties. However, they have a setback in terms of their thermal conductivity. Hence, this paper is made an attempt to improve the thermal properties of the paraffin by embedding nano-TiO2 particles in paraffin. Five samples of Nano Embedded Paraffin (NEP) were prepared by adding 0, 0.5, 1.0, 1.5 and 2.0 mass percentages of nano-TiO2 particles in paraffin and further investigated on their thermal properties using different instruments such as Fourier transform infrared spectrometer (FT-IR), thermogravimetric analyzer (TGA) and thermal properties analyzer. The results proved that the integration of nano-TiO2 particles enhanced the thermal conductivity of the paraffin to 33.889%, 66.111%, 84.444% and 101.667% for 0, 0.5, 1.0, 1.5 and 2.0 mass percentages, respectively, without disturbing its chemical structure. Further, nano-TiO2 particles delayed the thermal decomposition of paraffin and thereby, improved its thermal stability